Physiological Properties of Saccharomyces cerevisiae from Which Hexokinase II Has Been Deleted - Diderich, Jasper A. (American Society for Microbiology, 2001)
Hexokinase II is an enzyme central to glucose metabolism and glucose repression in the yeast Saccharomyces cerevisiae. Deletion of HXK2, the gene which encodes hexokinase II, dramatically changed the physiology of S. cerevisiae. The hxk2-null mutant strain displayed fully oxidative growth at high glucose concentrations in early exponential batch cultures, resulting in an initial absence of fermentative products such as ethanol, a postponed and shortened diauxic shift, and higher biomass yields. Several intracellular changes were associated with the deletion of hexokinase II. The hxk2 mutant had a higher mitochondrial H(+)-ATPase activity and a lower pyruvate decarboxylase activity, which coincided with an intracellular accumulation of pyruvate in the hxk2 mutant. The concentrations of adenine nucleotides, glucose-6-phosphate, and fructose-6-phosphate are comparable in the wild type and the hxk2 mutant. In contrast, the concentration of fructose-1,6-bisphosphate, an allosteric activator of pyruvate kinase, is clearly lower in the hxk2 mutant than in the wild type. The results suggest a redirection of carbon flux in the hxk2 mutant to the production of biomass as a consequence of reduced glucose repression.